The regulation of glutamatergic nervous system in sleep-wake states and general anesthesia - Wei Luo; Meiyi Duan; Enpeng Liang; Siwei Wang; Jie Yuan (Brain Research Bulletin, 2025)
The sleep-wake states and general anesthesia share many neurophysiological similarities, as both involve reversible changes in consciousness and modulation of brain activity. This paper reviews the role of glutamatergic neurons, the brain's primary excitatory neurons, in regulating sleep-wake states and general anesthesia. We discuss the involvement of glutamatergic neurons across various brain regions, including the brainstem, basal forebrain, thalamus, hypothalamus, and cortex, highlighting their contributions to physiological sleep-wake and anesthesia modulation. Recent advancements in techniques such as optogenetics, chemogenetics, and neural tracing have enhanced our understanding of these neurons' functions. Understanding these mechanisms can lead to improved therapeutic strategies for sleep disorders and more precise anesthetic practices, providing new avenues for clinical intervention.